Parental Genome Quality on the Character of Children with Down Syndrome (Educational Perspective) - Silva Ardiyanti (IAIN KENDARI, 2025)
The genome is a collection of genes in chromosomes that are dynamic, active and are the command centre in forming complex creatures. The purpose of this study is to obtain information about the role of genomes in differences in children's character, because the quality of parents' genes basically determines how the character of children has differences from one child to another. and Down syndrome children and provide early knowledge to people who are not yet married that the quality of their genes determines their next generation. The research uses a qualitative approach that is descriptive analysis. Data were collected using interview and documentation techniques. The research subjects consisted of 4 children with Down syndrome and 4 parents (mother and father). From the results of interviews conducted, the role of the environment on genome quality is very influential. Firstly, out of 4 pairs of families, only 1 respondent has a history of genetic disorders while the other 3 respondents do not. Second, the environment affects the inhibition and speed of recovery of Down syndrome children if they do not and or get the right treatment. Third, children with Down syndrome have an equal opportunity to succeed. These findings emphasise the important role of family and community education in supporting the overall growth and development of children.